2014
DOI: 10.5539/res.v6n2p95
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Social Support on Faculty Workload and Performance

Abstract: The current study has examined the interaction between social support and workload for predicting the work related performance of academic staff in Pakistan. A self administered questionnaire was distributed among a sample of 400 academic staff working in the six universities of Pakistan. Data was analyzed through multivariate statistics like Factor Analysis and Multiple Regression Analysis. The results of current study showed that workload was negatively related with the work performance, where social support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
(22 reference statements)
0
4
1
1
Order By: Relevance
“…Thus, front-liners should be able to cope with inadequate resources at their workplace which indeed affected their job performance. In contrast, the results of this study also explain that the relationship between job performance and workload was significant, positive, and moderate which is consistent to [11], and [23] study however inconsistent with [24]. Based on the findings, workload is positively associated with job performance, whereby front-liners must maintain their perceptions on workloads that enable them to increase their job performance.…”
Section: Correlation Between Each Component Of Job Stress and Job contrasting
confidence: 56%
“…Thus, front-liners should be able to cope with inadequate resources at their workplace which indeed affected their job performance. In contrast, the results of this study also explain that the relationship between job performance and workload was significant, positive, and moderate which is consistent to [11], and [23] study however inconsistent with [24]. Based on the findings, workload is positively associated with job performance, whereby front-liners must maintain their perceptions on workloads that enable them to increase their job performance.…”
Section: Correlation Between Each Component Of Job Stress and Job contrasting
confidence: 56%
“…Third, Zhou and Lin found that individuals with high levels of social support demonstrate a stronger positive adaptability-life satisfaction relationship among freshmen Chinese students at a university in China [72]. Fourth, it moderates the negative relationship between workload and performance among academic professionals [48], as well as the psychological capital-engagement relationship of students [12].…”
Section: Hypothesis Developmentmentioning
confidence: 97%
“…Social support is a psychosocial resource, where good interactions lead to good social support when needed. However, such support cannot be fully received if an individual's social interaction skills are limited or weak [48]. The positive and healthy influence of social work support in the organization is justified from three perspectives.…”
Section: Social Work Supportmentioning
confidence: 99%
“…Menurut penelitian yang dilakukan oleh Yusoff et al, (2014) bahwa jika beban kerja melebihi kemampuan karyawan maka hasilnya akan menurun kinerjanya.…”
Section: Dukungan Sosialunclassified